Defects identification of the main gas pipelines - Banakhevych, Yu. V.; Banakhevych, R. Yu. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
This paper describes a typical case of diagnosing and determining the causes of the formating of longitudinal cracks on the outer surface of the pipe, analyzes the current state of diagnosis of main gas pipelines. There is shown the importance of timely and correct response to diagnostic results. There is considered the experience in carrying out measures to optimize the repair processes of main gas pipelines by clearly establishing the timing of both evaluating the results of internal pipe diagnostics and the formating of repair plans, substantiating the criteria for choosing defects for repair and establishing a unified approach to the process, including technical documentation.